Working conditions and wellbeing in UK social workers. (September 2021) - Ravalier, Jermaine; Wainwright, Elaine; Clabburn, Oliver; Loon, Mark; Smyth, Nina
Summary: UK social workers are exposed to chronically poor working conditions and experience extremely high levels of sickness absence. The aim of this study was to gain an in-depth understanding of working conditions and wellbeing of social workers. Seven UK social work employers sent a survey of working conditions, wellbeing, and turnover intentions to all child and family social workers, followed by a series of individual semi-structured interviews with respondents. Data were collected between January and May 2019. Six hundred and seventy-six (41% response rate) completed surveys were returned and 19 interviews undertaken. Findings: Quantitative findings demonstrated that working conditions scored better than previous studies, with positive scores on autonomy, peer, and managerial support. However, the four remaining conditions (demands, relationships, role, and change) each scored worse than 75–90% of respondents in UK-wide benchmarks of individuals from various occupations. Regression outcomes demonstrated that demands, control, change, relationships, and peer support each significantly impacted employee wellbeing. Furthermore, over 20% of respondents suggested that they were frequently exposed to poor service user behaviour. Thematic analysis of interviews suggested that workload (demands), relationships with peers, management, and services users, and the way in which change was communicated were the main difficulties cited. Applications: It is clear that work is needed to support social worker stress and wellbeing at work. Management should support individuals in terms of developing peer and managerial support, and adopting best practice in reflective supervision. Furthermore, a more robust system of caseload allocation would support and improve significant workload pressures.